2020
DOI: 10.1016/j.devcel.2020.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Lamin A/C in the Nuclear Interior Binds Active Enhancers Associated with Abnormal Transcription in Progeria

Abstract: LMNA encodes nuclear lamin A/C that tethers lamina-associated heterochromatin domains (LADs) to the nuclear periphery. Point mutations in LMNA cause degenerative disorders including the premature aging disorder Hutchinson-Gilford progeria, but the mechanisms are unknown. We report that Ser22phosphorylated Lamin A/C (pS22-Lamin A/C) was localized to the interior of the nucleus in human fibroblasts throughout the cell cycle. pS22-Lamin A/C interacted with a specific subset of putative active enhancers, not LADs,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 92 publications
(132 reference statements)
4
88
0
Order By: Relevance
“…1G), although for Lamin A/C we observed a somewhat smaller dynamic range. This may be due to some interactions of Lamin A/C with inter-LAD regions [31,32]. Together, these results show that pA-DamID can be used to map NL associations effectively.…”
Section: Genome-wide Pa-damid Maps Are Reproducible and Specificmentioning
confidence: 72%
“…1G), although for Lamin A/C we observed a somewhat smaller dynamic range. This may be due to some interactions of Lamin A/C with inter-LAD regions [31,32]. Together, these results show that pA-DamID can be used to map NL associations effectively.…”
Section: Genome-wide Pa-damid Maps Are Reproducible and Specificmentioning
confidence: 72%
“…G. Lund, Duband-Goulet, Oldenburg, Buendia, & Collas, 2015) and affect their epigenetic landscape (Bianchi et al, 2020; Briand et al, 2018; Cesarini et al, 2015; Oldenburg et al, 2017). Furthermore, lamin A/C has also been shown to directly interact with promoters and enhancers and seems to be involved in both positive and negative gene regulation (Ikegami et al, 2020; E. Lund & Collas, 2013; E.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that gene regulatory pathways have to be highly flexible and dynamic to respond efficiently to internal and external cues and thus require a dynamic lamin complex that can dynamically associate with and regulate chromatin. Indeed, loss of LAP2α (Gesson et al, 2016) or disease-linked mutations in lamins (Bianchi et al, 2020; Briand et al, 2018; Ikegami et al, 2020; Oldenburg et al, 2017) affect epigenetic regulation and/or gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that lamins are notoriously insoluble, form filaments and lack any catalytic activity led to the initial notion that lamins function primarily to maintain nuclear shape and integrity. However, research in the past 20 years demonstrated that lamins play a crucial role in various cellular processes including mechanotransduction, modulation of nuclear stiffness and elasticity, chromatin organization, DNA replication and repair, and transcriptional regulation [4,17,18].…”
Section: The Nuclear Laminamentioning
confidence: 99%